Veniss underground - VanderMeer, Jeff (Tor, 2003)
On a far-future Earth, the mysterious Quin manipulates biological engineering to create sentient species as both toys and manual labour. When Nicholas, a failed holo artists, decides to visit Quin, he discovers just how dangerous it is to know him, in the place known as Veniss Underground.